Efektivitas Layanan Bimbingan dan Konseling dalam Mengatasi Permasalahan Belajar Siswa: Kajian Literatur - Sofia Maharani; Zulfa Nurfadhilah Ardalia Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
Education is a crucial aspect for individuals; however, in reality, many students face learning obstacles such as low motivation and academic procrastination, which can hinder their psychological development. This literature review aims to analyze the effectiveness of various Guidance and Counseling (GC) services in addressing students’ learning problems and to identify the most prevalent and efficient strategies. The research method used was a literature review of 20 scientific articles from accredited journals and academic books published over the past ten years. Data analysis was conducted thematically to map patterns and trends in the effectiveness of interventions. The results indicate that GC services significantly contribute to addressing learning difficulties through four primary models: group counseling, individual counseling, classroom guidance, and comprehensive services. Group counseling was found to be the most widely used and effective service in enhancing students’ learning motivation and social interaction through group dynamics. Meanwhile, individual counseling proved effective for addressing personal and specific issues such as truancy and procrastination. Although effective, the implementation of guidance and counseling services still faces challenges in the form of a limited number of counselors and suboptimal time management. The implications of this study emphasize the need to optimize group services as a primary strategy, as well as increased support from schools and parents to create preventive and comprehensive interventions.